Comparison of fuel consumption of diesel jeepney and auto-LPG jeepney in Litex-San Isidro (Rodriguez) route - Sia, Heimer D.; Vergel, Karl B. N.; Abaya, Ernesto B. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The main purpose of this study is to determine the fuel consumptions of a diesel jeepney and an auto-LPG jeepney. This is to find out which of these jeepneys is better suited for public transportation. This will help the jeepney drivers who are struggling to earn an income from the increasing price of diesel. Several factors are considered on what can affect the fuel consumption of a vehicle. Some of these include the passenger load, the average speed, and idle time. An on-road test is conducted for these two jeepneys for duration of 7 days. Some of the information gathered are boarding and alighting survey, and fuel consumption suney. A GPS is used for determining the length, and duration of the trip The idle time and the average speed can be identified from the gathered data. These data are transferred to software called Garmin Basecamp. Correlations are done between these factors for comparisons. Results have shown that speed does not nor has litlle effect fuel consumption much. Increase idle time can cause higher fuel consumption however. In terms of economy, diesel appears to be more ecollomi calthan auto-LPG.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman